Penerapan Metode Diskusi dalam Meningkatkan Motivasi Belajar Siswa pada Pembelajaran Tematik - Zaeni, Abu (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2021)
The discussion method is a way or approach that can be applied by an educator in the classroom with the aim of solving problems through the exchange of arguments, opinions, and achieving consensus and agreement from learners. The objectives of this research are: 1) To identify the steps of the discussion method in enhancing the learning motivation of students in class 2B at SD Islam NU Sekaran. 2) To determine the inhibiting factors of applying the discussion method in improving the learning motivation of students in class 2B at SD Islam NU Sekaran. The research method used in this study is qualitative with a descriptive research type, which is a research procedure or problem-solving investigated with a description of the subjects or objects used, such as individuals, institutions, communities, and others. Data collection methods used include interviews, observations, and documentation. The research results are as follows: 1) Discussion method steps: The teacher introduces the problem, students identify the core issue. Students form groups with individual tasks and teacher guidance. Students actively engage in the group, and the teacher maintains order and provides support. Each group presents a report, is responded to by other groups, and receives feedback from the teacher. The groups record the discussion results collected by the teacher. The teacher reads the discussion results, makes corrections, and provides assessments. The entire process serves as a basis for improvement in future discussions. 2) Inhibiting factors: Less active group members can hinder the method. The presence of the teacher has a significant impact. Extensive material can prolong the discussion. Dominance by vocal students creates imbalance. There is potential for emotional reactions if opinions are not accepted.